Hole Matrix Mapping Model for Partitioned Sitting Surface Based on Human Body Pressure Distribution Matrix - Lu, Chunfu; Chen, Zeyi; Li, Yu; Fu, Xiaoyun; Tang, Yuxiao (Healthcare (Basel), 2023)
(1) Objective: The objective of this study was to experimentally obtain the ideal pressure distribution model of buttock and thigh support for office workers in forward-leaning and upright sitting postures, reproduce the support provided by mesh materials with elastic materials, and propose an effective seat design scheme to improve the comfort of office workers. (2) Method: Based on the seven most popular mesh chairs on the market, pressure distribution experiments, and the fuzzy clustering algorithm, the relatively ideal body pressure distribution matrices were generated for office workers under two common sitting postures, and the corresponding partitioned sitting support surfaces were obtained. A prototype chair was created and validated by combining the ergonomics node coordinates and the physical properties of the materials. (3) Result: An ideal support model of four zones was constructed, and prototype pads were designed and produced according to this model. Subjects were recruited to test the ability of the prototypes to reproduce the ideal pressure distribution maps. (4) Conclusion: The four-zone ideal support model is capable of effectively representing the buttock and thigh support requirements in forward-leaning and upright sitting postures, and it is useful for the development of related products. Studying sitting postures and pressure values generated by different activities of office workers will help to refine the needs of office personnel and provide new ideas for the design of office chairs.